Static and dynamic Raman excitation mapping of chirality-pure carbon nanotube films - Paul Finnie; Jianying Ouyang; Jeffrey A. Fagan (Communications Materials)
Abstract Raman spectroscopy is a powerful method for probing electronic and vibrational properties of materials, particularly nanomaterials such as single-wall carbon nanotubes. Typically, Raman spectroscopy is conducted at a single, or few, excitation wavelengths, but that provides limited information about excitation resonance structure, and their dynamical evolution. Here, we extend a sensitive full-spectrum technique to rapidly obtain two-dimensional Raman excitation maps both statically and dynamically for chirality-pure single-wall carbon nanotube films. We demonstrate sensitive evaluation of structured resonance profiles even from weak vibrational modes, and sub-second time resolution of the dynamics of photo-driven defect production. Findings include the direct observation of bands and their profiles – including bands which could be missed in conventional Raman spectroscopy - and demonstration of differences for odd vs. even defect band combinations. This opens up possibilities to investigate the coupling of electronic states with vibrational modes in nanomaterials and track their dynamical evolution subject to intentional modulation.